Subjectivity About Turnover Intention Among Male Nurses in South Korea: A Q-Methodological Study - Ick-Jee Kim; Hyung-Wha Shim (Elsevier, 2018)
Purpose: Around the world, male nurses face a variety of difficulties within clinical settings; accordingly, a large number of male nurses consider changing their occupation. In particular, male nurses in a number of Asian countries with a Confucian heritage experience difficulties. Thus, the purpose of this study was to explore individual differences in turnover intention among male nurses in one such country, South Korea, and on that basis to suggest concrete strategies for reducing turnover among male nurses in Confucian cultures. Methods: Q methodology, which is used to analyze human subjectivity, was applied. Q statements were derived from 207 candidate statements gathered from various documents and interviews; 40 statements were finalized. A purposive sample of 41 male nurses was selected as likely to have diverse opinions on turnover intention of male nurses. The collected data were analyzed using PQMethod software. Results: Four distinct types of subjectivity about turnover intention among male nurses were identified: (1) "Pursuing occupational values," (2) "Dissatisfaction with treatment," (3) "Seeking a relaxed and stable life," and (4) "Conflict related to organizational culture." Conclusion: This study suggests various ways of reducing turnover and increasing retention among male nurses based on the four identified perspectives, especially in Confucian heritage regions. Keywords: confucianism, male, nurses, perception, personnel turnover